Perancangan Sistem Informasi Manajemen Inventaris Kontrol Stok Barang Berbasis Web - Kurniawati, Evi; Ikhwan, Ali (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
PT. Florindo Makmur is a company that processes cassava into tapioca flour into finished products. This company still has a number of problems that occur due to document processing that goes from one party to another. Document approval processes, for example purchase requisitions, are slow and long, this is because the employee is on leave or out of town, thus causing the required signature to take a long time and while the employee is at the workplace. Referring to these various problems, researchers identify problem solving whose goal is to improve the company's business processes. This company developed a supply chain management information system using steps including: analyzing the business stages that run there, analyzing problems that arise in the procurement stage and thinking about what effects and limitations arise when implementing SCM. SCM is the process of supply chain management, starting from the source of raw materials, through production, until the final product reaches the hands of the customer. One of the objectives of implementing SCM in corporate is to build good cooperation with suppliers. One possibility is the implementation of SCM. With this implementation, the process of purchasing raw materials becomes easier and good corporate relations can be established. In addition, internal corporate aspects such as production must also be considered. Delivery and services offered to consumers must be considered so that they feel comfortable. In establishing this system, researchers used MYSQL for the database, programming languages via PHP and HTML, and the waterfall method as planning and problem formulation.